2016
DOI: 10.1080/21541248.2016.1205334
|View full text |Cite
|
Sign up to set email alerts
|

Arg188 drives RhoC membrane binding

Abstract: RhoA and RhoC GTPases are 92% identical but demonstrate unique regulation and function. Phosphorylation of Ser188 has widely been reported to inhibit RhoA activity. RhoC possesses Arg188 in place of Ser188 but retains a canonical upstream PKA recognition sequence. We report here that RhoC-R188S was a PKA substrate in vitro and exhibited less GTP loading compared to wild-type RhoC when expressed in cells. Transiently expressed RhoC was found to be significantly more membrane associated than RhoA. Membrane assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Further studies should identify the specific GEFs and GAPs for RhoC to better understand the molecular details of the signal transduction pathway during phagosome formation. Recently, Patel et al have reported that RhoC shows a higher degree of membrane association than does RhoA (Patel et al, 2016). In their study, these authors demonstrated that arginine 188 of RhoC promotes membrane binding.…”
Section: Discussionmentioning
confidence: 94%
“…Further studies should identify the specific GEFs and GAPs for RhoC to better understand the molecular details of the signal transduction pathway during phagosome formation. Recently, Patel et al have reported that RhoC shows a higher degree of membrane association than does RhoA (Patel et al, 2016). In their study, these authors demonstrated that arginine 188 of RhoC promotes membrane binding.…”
Section: Discussionmentioning
confidence: 94%
“…31 Within the RhoA/ROCK signaling pathway, RhoA phosphorylation at Ser188 directly inhibits RhoA activity, aligning with the findings of our study. 32,33 Moreover, this phosphorylation of RhoA serves as a key protective mechanism against RhoAmediated vascular remodeling. 34 In this study, we first investigated whether H 2 S could promote RhoA phosphorylation at Ser188, thereby inhibiting the activity of the RhoA/ROCK pathway in vivo.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Within the RhoA/ROCK signaling pathway, RhoA phosphorylation at Ser188 directly inhibits RhoA activity, aligning with the findings of our study. 32 , 33 Moreover, this phosphorylation of RhoA serves as a key protective mechanism against RhoA-mediated vascular remodeling. 34 …”
Section: Discussionmentioning
confidence: 99%
“…It is widely recognized that phosphorylation of RhoA at Ser188 directly inhibits RhoA activity 35 , but phosphorylation at Ser88 increases its activity 36 . In the present study, we demonstrated that RhoA activity is significantly inhibited in HNCs after phosphorylation at Ser188, which is consistent with previous results 37 .…”
Section: Discussionmentioning
confidence: 99%